2016
DOI: 10.1002/ece3.2458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogeography of Siberian roe deer, Caproulus pygargus, in central and peripheral populations

Abstract: Current understanding of phylogeographical structure and genetic diversity of Siberian roe deer remains limited mainly due to small sample size and/or low geographical coverage in previous studies. Published data suggest at least two phylogroups: western (Ural Mountains and Western Siberia) and eastern (east from lake Baikal, including the Korean peninsula), but their phylogenetic relationship remains unclear. Combined sequences of cytochrome b (1140 bp) and the mtDNA control region (963 bp) were analyzed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…There has been much debate about the phylogenetic and taxonomic position of this species. Once considered a single species covering most of the Eurasia, it is now widely accepted that roe deer is divided into two allopatric species: the European roe deer C. capreolus, distributed over most of Europe and a few Mediterranean islands, and the Siberian roe deer C. pygargus, ranging from the Eastern Europe to the continental Asia (Lee et al, 2016). The two species are geographically separated by the physical barrier of the Urals.…”
Section: Application Of Minosse To Real Case Studiesmentioning
confidence: 99%
“…There has been much debate about the phylogenetic and taxonomic position of this species. Once considered a single species covering most of the Eurasia, it is now widely accepted that roe deer is divided into two allopatric species: the European roe deer C. capreolus, distributed over most of Europe and a few Mediterranean islands, and the Siberian roe deer C. pygargus, ranging from the Eastern Europe to the continental Asia (Lee et al, 2016). The two species are geographically separated by the physical barrier of the Urals.…”
Section: Application Of Minosse To Real Case Studiesmentioning
confidence: 99%
“…In the Republic of Korea, the Siberian roe deer lives on the Korean peninsula and Jeju Island, and is considered a subspecies of Siberian roe deer, Capreolus pygargus tianschanicus Satunin, 1906 [5] or Capreolus pygargus bedifordi Thomas, 1908 [9]. However, several recent genetic and morphological studies have suggested that the roe deer on Jeju Island (Jeju roe deer [JRD]) is different from the roe deer on the Korean peninsula (mainland roe deer [MRD]) [13, 15, 16, 19,20,21]. The JRD has a smaller body and skull than the MRD [19,20,21] and is genetically more similar to populations in western Siberia than those in the Far East [13, 15, 16].…”
mentioning
confidence: 99%
“…However, several recent genetic and morphological studies have suggested that the roe deer on Jeju Island (Jeju roe deer [JRD]) is different from the roe deer on the Korean peninsula (mainland roe deer [MRD]) [13, 15, 16, 19,20,21]. The JRD has a smaller body and skull than the MRD [19,20,21] and is genetically more similar to populations in western Siberia than those in the Far East [13, 15, 16]. Therefore, the possibility that the JRD belongs to the subspecies Capreolus pygargus ochracean , not C. p. tianschanicus , has been suggested [13].…”
mentioning
confidence: 99%
See 2 more Smart Citations